2019
DOI: 10.1002/xrs.3101
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic examination of the 2,300‐year‐old excavated steel plowshare from northern India

Abstract: In the present investigation, X‐ray diffractometer, optical microscope, and scanning electron microscope were used to analyze the plowshare excavated from Ganwaria, UP, India. The main objective of the investigation was to determine the type of alloy, analysis of slag inclusion, and corrosion behavior. X‐ray diffraction analysis showed the presence of α‐iron. Microstructure consists of ferrite and pearlite grains; ferrite phase was soft in comparison to the pearlite. Optical micrograph at lower magnification r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A number of artefacts have been analysed for composition to determine the extent of alloying in iron. Singh et al (2019) examined an excavated steel ploughshare from Ganwaria, Uttar Pradesh, in north India. It was revealed that the tool was manufactured from carbon steel with evidence of slag inclusion (Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of artefacts have been analysed for composition to determine the extent of alloying in iron. Singh et al (2019) examined an excavated steel ploughshare from Ganwaria, Uttar Pradesh, in north India. It was revealed that the tool was manufactured from carbon steel with evidence of slag inclusion (Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2019) examined an excavated steel ploughshare from Ganwaria, Uttar Pradesh, in north India. It was revealed that the tool was manufactured from carbon steel with evidence of slag inclusion (Singh et al, 2019). An ancient sword made of wootz steel from Karnataka was examined by Barnett and Balasubramaniam (2007) using Electron Backscatter Diffraction (EBSD).…”
Section: Introductionmentioning
confidence: 99%